Optimal discretization of Ill-posed problems - Pereverzev, S. V.; Solodkii, S. G. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We present a survey of results on the optimal discretization of ill-posed problems obtained in the Institute of Mathematics of the Ukrainian National Academy of Sciences.